2015
DOI: 10.1590/0103-8478cr20140853
|View full text |Cite
|
Sign up to set email alerts
|

Níveis de fitase sobre o desempenho, parâmetros ósseos e bioquímicos de suínos alimentados com ração de origem vegetal sem inclusão de fosfato bicálcico

Abstract: RESUMO Este estudo foi conduzido com o objetivo de avaliar os

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
2
0
3
Order By: Relevance
“…However, it can be inferred that acidity caused by the dissociation of butyric acid resulted in a lower deposition of calcium and phosphorus in the bones, considering the result observed for the raw bones, even with the addition of phytase in the diets. Magnago et al (2015) noted that the phytase concentration does not influence the levels of ash and phosphorus in the metacarpals of the animals. Saraiva et al (2009) reported that animals genetically selected for muscle deposition favor weight gain at the expense of bone integrity when subjected to phosphorus deficiency.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, it can be inferred that acidity caused by the dissociation of butyric acid resulted in a lower deposition of calcium and phosphorus in the bones, considering the result observed for the raw bones, even with the addition of phytase in the diets. Magnago et al (2015) noted that the phytase concentration does not influence the levels of ash and phosphorus in the metacarpals of the animals. Saraiva et al (2009) reported that animals genetically selected for muscle deposition favor weight gain at the expense of bone integrity when subjected to phosphorus deficiency.…”
Section: Resultsmentioning
confidence: 97%
“…Freitas et al (2006) reported a superior consistency of feces from piglets at 21-49 days of age when organic acids were used in the diet. Papatsiros et al (2011) evaluated benzoic acid in the feed of weaned piglets and found a reduction in the severity of diarrhea.…”
Section: Resultsmentioning
confidence: 99%
“…São proteínas globulares de estrutura terciária ou quaternária que atuam como catalisadores biológicos que aceleram as reações químicas e têm alta especificidade, pois cada tipo de enzima atua sobre um composto ou substrato associado, que se encaixa na enzima específica, de modo que os centros ativos coincidem perfeitamente, sendo capazes de abrir caminhos para sua transformação (complexo enzimasubstrato) (Magnago et al, 2015).…”
Section: Enzimas Na Nutrição Animalunclassified
“…As enzimas exógenas não são organismos vivos, mas produtos de organismos vivos como bactérias e fungos. São proteínas globulares de estrutura terciária ou quaternária que atuam como catalisadores biológicos que aceleram as reações químicas e têm alta especificidade, pois cada tipo de enzima atua sobre um composto ou substrato associado, que se encaixa na enzima específica, de modo que os centros ativos coincidem perfeitamente, sendo capazes de abrir caminhos para sua transformação (complexo enzimasubstrato) (Magnago et al, 2015).…”
Section: Enzimas Na Nutrição Animalunclassified